PENGARUH GCG, UKURAN PERUSAHAAN, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS - Dimas Wahyul Muslimin; Syaiful Bahri (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to analyze the effect of GCG, company size, sales growth on financial distress. Financial distress is a situation where a company can go bankrupt because it cannot fulfill its obligations and has a small profit. The research population is banking sector entities for the period 2019 – 2020. Non-probability sampling technique using purposive sampling method with a total of 29 entities. The data analysis technique used is multiple regression analysis. The results show that GCG and sales growth variables have a significant effect on financial distress, meaning that management involvement and sales growth greatly affect financial distress. Company size has no effect on financial distress